2022
DOI: 10.3389/fphar.2022.1039499
|View full text |Cite
|
Sign up to set email alerts
|

Metal-dependent programmed cell death-related lncRNA prognostic signatures and natural drug sensitivity prediction for gastric cancer

Abstract: Background: Gastric cancer is one of the most important malignancies with poor prognosis. Ferroptosis and cuproptosis are newly discovered metal-dependent types of programmed cell death, which may directly affect the outcome of gastric cancer. Long noncoding RNAs (lncRNAs) can affect the prognosis of cancer with stable structures, which could be potential prognostic prediction factors for gastric cancer.Methods: Differentially expressed metal-dependent programmed cell death (PCD)-related lncRNAs were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…Our study also indicated that CDI score could potentially function as a predictor of drug sensitivity for certain FDA-approved drugs, such as Olaparib and Oxaliplatin. This aligns with prior research suggesting that PCD-related genes are associated with drug sensitivity in diverse cancer types, including ovarian cancer and colorectal cancer [ 26 28 ]. However, our study had its basis on in silico analysis, and additional experimental validation is essential to assess the clinical applicability of our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Our study also indicated that CDI score could potentially function as a predictor of drug sensitivity for certain FDA-approved drugs, such as Olaparib and Oxaliplatin. This aligns with prior research suggesting that PCD-related genes are associated with drug sensitivity in diverse cancer types, including ovarian cancer and colorectal cancer [ 26 28 ]. However, our study had its basis on in silico analysis, and additional experimental validation is essential to assess the clinical applicability of our findings.…”
Section: Discussionsupporting
confidence: 89%
“…Excitingly, a range of gene models centered around programmed cell death (such as ferroptosis and cuprotosis) have been developed. [21][22][23][24][31][32][33] These models hold great promise in identifying potential targets for therapeutic interventions in GC.…”
Section: Discussionmentioning
confidence: 99%
“…This area represents a new research direction in GC. [21][22][23][24] One novel and less explored mechanism of programmed cell death is the discovery of disulfidptosis this year. Researchers have observed that during glucose starvation, an abnormal accumulation of intracellular disulfide bonds disturbs the normal disulfide bonds between cytoskeletal proteins, ultimately leading to cell death.…”
Section: Introductionmentioning
confidence: 99%
“…It can circumvent the limitations of individual lncRNAs in predicting prognosis, but also avoid the defects of interactions among lncRNAs. Currently, studies on the prognostic signature of Cuproptosis-associated lncRNAs have been conducted in tumors such as bladder cancer ( 53 ), head and neck squamous cell carcinoma ( 54 ), and gastric cancer ( 55 ). However, most studies have used co-expression analysis for screening of lncRNAs, but few studies have systematically explored the genes from which lncRNAs originate, as well as their distribution and expression differences at the single-cell level.…”
Section: Discussionmentioning
confidence: 99%